Does the stereotypicality of mothers’ occupation influence their children’s career aspirations? ... - Thorsteinsen, Kjærsti; Kvalø, Marie; Martiny, Sarah E.; Olsen, Marte (OSF Registries, 2020)
Career development is shaped throughout life, and already starts in infancy. There is relatively little knowledge about the predictors of career aspirations in childhood. Therefore, the present study aims to contribute to a better understanding of which factors play a role in shaping career aspirations in children’s childhood. In the present study we will investigate if the stereotypicality of mothers` occupations (female dominated, male dominated, or neutral) influences their children’s career aspirations. Data from a study conducted in kindergartens in Northern Norway (Tromsø) in 2018 (sample 1), were combined with data collected in elementary schools in Norway in 2020 (sample 2). This resulted in a sample of 72 child-mother dyads from the kindergartens (age range: 4 to 6 years) and 87 child-mother dyads from the elementary schools (age range: 6 to 13 years; total sample 159 child-mother dyads). We aim to replicate previous findings that show that the stereotypicality of mothers’ occupation influenced ...